Poglądy Tadeusza Bilikiewicza na zagadnienia alkoholizmu w Polsce - Ryszard Kujawski (Alcoholism and Drug Addiction, 2015)
The aim of this article is to present Professor Tadeusz Bilikiewicz's (1901–1980) views on the problem of alcohol in Poland. Medical literature articles and Gdańsk Library of the Polish Academy of Sciences documents were major sources of research. Tadeusz Bilikiewicz unsuccessfully tried to introduce a very radical form of counteracting alcoholism – the Prohibition Act. Attempts to introduce it received a negative reception in numerous environments.